Impact of Interactive Learning Environments on Learning and Cognitive Development of Children With Special Educational Needs: A Literature Review - Ugalde, Leire; Santiago-Garabieta, Maite; Villarejo-Carballido, Beatriz; Puigvert, Lídia (Frontiers in Psychology, 2021)
Children with special educational needs (SEN) achieve lower educational levels than their peers without special needs, leading to a higher risk of social exclusion in the future. Inclusive education aims to promote learning and to benefit the cognitive development of these students, and numerous research studies have indicated that interactive environments benefit inclusion. However, it is necessary to know how these inclusive environments can positively impact the academic improvement and development of these students' cognitive skills. This article provides a review of the scientific literature from Web of Science, SCOPUS, ERIC and PsychINFO to understand the impact of interactive environments on the academic learning and cognitive skill development of children with SEN. A total of 17 studies were selected. Those studies showed the effectiveness of interactive learning environments in promoting instrumental learning, increasing academic involvement, and improving the cognitive development of children with disabilities. Based on these results, it can be concluded that interaction-based interventions with an inclusive approach nurture the learning and cognitive development of students with SEN.